Buttram gets art spotlight at gallery (Raton, NM Raton Range, 1995)
Article is about Maroc Buttram being featured at the Old Pass Gallery
Newspaper article
Master list item #: 60
File location is in the Raton file Cabinet
Keywords: Buttram, Marco -- Student Artist; Old Pass Gallery; New Mexico Arts Division -- Sponsor; Santa Fe Pacific Foundation -- Sponsor; Art Shows; Art Exhibits; Art Sudents; Student Corner; Raton, New Mexico